Biocultural homogenization in elementary education degree students from contrasting ecoregions of Chile - Mendez-Herranz, Manuela; Ibarra, Jose Tomas; Rozzi Marin, Ricardo Roberto; Marini, Guillermo (My University, 2023)
Biocultural homogenization is a wicked problem that implies the loss of biological and cultural diversity at different scales. It is promoted by globalized one-dimensional ways of thinking that ignore the biophysical and cultural singularities of the heterogeneous regions of the planet. In Chile, we find ecoregions as diverse as the arid Norte Grande, the semi-arid Mediterranean Metropolitan region, and the temperate rainforests in the south. We studied the perceptions that elementary education degree students (EEDS) have regarding the flora and fauna (co-inhabitants), their environments (habitats), and their daily customs or activities (habits) in these three ecoregions. We distributed 72 questionnaires to students from 3 universities in 2021, asking them about co-inhabitants, habitats, and habits. We identified similarities and differences between the responses. Similarities were associated with biocultural homogenization processes evidenced by the prevalence of vertebrate animals and vascular plants, or introduced species, such as domestic animals, and cultivated plants for edible, ornamental, and medicinal purposes. Differences were associated with biocultural conservation processes such as the collection of native species of mushrooms, plants and animals for food use, or the knowledge of ritual celebrations typical of their localities. We propose that teaching study programs should aim to redirect biocultural homogenization processes toward biocultural conservation processes. That way teachers can play a key role in teaching future generations to learn and value both local and scientific knowledge about the diversity of co-inhabitants, habitats, and the life habits in each of their ecoregions.
Keywords: biocultural ethics; biodiversity perceptions; everyday aesthetics; extinction of experience; teacher education